Manajemen Sumber Daya Manusia Berbasis Spiritual Company (Studi Kasus Di Namu Tuang Café & Resto Sukabumi) - Virgiawan, Rheyza; Achmad, Syaifullah (Yayasan Rahmat Islamiyah, 2023)
Human resource management is a process of utilizing workforce that is carried out effectively and efficiently through planning, mobilization and control activities. Spiritual Company is a company or organization with all stakeholders whose work practices adhere to the principles of noble values of spirituality in each employee with a spirit of worship based on the Al-Quran and Sunnah in carrying out all company activities and developing activities to increase knowledge of religion. This research is qualitative research, with data collection methods using observation, documentation and in-depth interviews. This research was conducted at Namu Tuang Café Resto which is located in Gunung Jaya Village, Cisaat District, Sukabumi Regency. The results of this research show that (1) human resource management at Namu Tuang Café Resto Sukabumi has been implemented well based on management functions, namely planning, recruitment, selection, work contracts, work assessment, compensation and dismissal. (2): The implementation of the company's spiritual program at Namu Tuang Café Resto Sukabumi is oriented towards three categories, namely, aqidah values, worship values, and moral values. The benefits obtained through instilling aqidah values are the spirit of working for Allah. In cultivating the value of worship, namely prioritizing a disciplined and responsible attitude. Meanwhile, in terms of moral values and attitudes, it becomes better, especially in character formation.